Influence of Adolescent Reproductive Health Promotion Media Booklet on Knowledge and Attitude of Adolescents Living in Work Area of Ibrahim Adjie Public Health Center in 2018 - Sri Hennyati Amiruddin; Sri Komalaningsih; Ma'mun Sutisna; Hidayat Wijayanegara; Leri Septiani; Herry Garna (Global Medical & Health Communication, 2020)
Adolescent period is a critical period that requires quality health services. The aim of this study was to analyze the effect of health education through booklet media on the knowledge and attitude towards reproductive health among adolescents. This was a quasi-experimental case control study with nonequivalent two group design conducted on 282 students of SMP Negeri 37, a public junior high school, in the work area of Ibrahim Adjie Public Health Center in Bandung city during December 2018–May 2019. Subjects were divided into two groups, intervention and control groups, with 141 subjects in each group. Data collected were tested for normality and homogeneity using Kolmogorov-Smirnov and Levene tests, respectively, followed by a bivariate analysis using Wilcoxon test to determine the difference. Knowledge of all students in both groups was poor during pre-test with an increase found in 135 subjects (95.7%) in the intervention group (p=0.001) and 63 subjects (44.7%) in the control group (p=0.003) based on the post-test results. Negative attitude was also seen in both groups during pre-test, with a shift towards positive attitude was evident in 134 students (95.0%) in the intervention group (p=0.001) and 117 students (83.0%) in the control group (p=0.002) based on post-test results. This presence that health information conveyed through booklet has a probability of giving 0.995 times stronger influence leaflet. Thus, the use of booklet can improve knowledge and attitude towards adolescent reproductive health.